A small RNA mediated regulation of a stress-activated retrotransposon and the tissue specific transposition during the reproductive period in Arabidopsis - Matsunaga, Wataru; Ohama, Naohiko; Tanabe, Noriaki; Masuta, Yukari; Masuda, Seiji; Mitani, Namiki; Yamaguchi-Shinozaki, Kazuko; Ma, Jian F.; Kato, Atsushi; Ito, Hidetaka (Frontiers in Plant Science, 2015)
Transposable elements (TEs) are key elements that facilitate genome evolution of the host organism. A number of studies have assessed the functions of TEs, which change gene expression in the host genome. Activation of TEs is controlled by epigenetic modifications such as DNA methylation and histone modifications. Several recent studies have reported that TEs can also be activated by biotic or abiotic stress in some plants. We focused on a Ty1/copia retrotransposon, ONSEN, that is activated by heat stress in Arabidopsis. We found that transcriptional activation of ONSEN was regulated by an siRNA-related pathway, and the activation could also be induced by oxidative stress. Mutants deficient in small interfering RNA (siRNA) biogenesis that were exposed to heat stress at the initial stages of vegetative growth showed transgenerational transposition. The transposition was also detected in the progeny, which originated from tissue that had differentiated after exposure to the heat stress. The results indicated that in some undifferentiated cells, transpositional activity could be maintained quite long after exposure to the heat stress.